Corruption and Democracy in Middle East and North Africa Countries: Dynamic Generalized Method of Moments - Lazreg, Mohammed; Mohammed, Kamel Si (International Journal of Economics and Financial Issues, 2019)
The goal of this study is to investigate the relationship between democracy and corruption using a Dynamic Generalized Method of Moments (DGMM) during the period 1984-2013 in 13 MENA countries namely Algeria, Bahrain, Egypt, Iraq, Iran, Kuwait, Lebanon, Morocco, Qatar, Saudi Arabia, Tunisia, Turkey and United Arab Emirates. Our results captured the GDP per capita is feed corruption in MENA countries, while one percent of per capita GDP rise corruption about 0.73 and lead to lose more than 0.23 in MENA net oil and gas exporting countries except United Arab Emirates (Omgba (2015); Haber and Menaldo (2011)). In this context, magnitude of impacts in countries non-oil producers is less dependent with corruption over the last decade compared the two early decades and compares an oil and gas exporting countries. Thus, the high income states of the oil exporting countries would not have been decreased corruption level (Jetter (2015), Rachdi and Saidi (2014)). Finally, our finding present a positive significantly associated between democracy and corruption, the influence of positive feedback around about 0.5 points in regressors. According to this estimation, the lower democratization process in MENA countries highly depends to high levels of corruption Keywords: Corruption, Democracy, MENA Countries, Panel GMM JEL Classifications: F2, C3 DOI: https://doi.org/10.32479/ijefi.7239